![16 - 2 \sqrt{20} - 2 \sqrt{28} + 2 \sqrt{35} 16 - 2 \sqrt{20} - 2 \sqrt{28} + 2 \sqrt{35}](https://tex.z-dn.net/?f=16+-+2+%5Csqrt%7B20%7D++-+2+%5Csqrt%7B28%7D++%2B+2+%5Csqrt%7B35%7D+)
Answers
Answered by
1
Answer:
16 -2√20 - 2√28 - 2√35
= 16-2(√(5×4)) - 2(√(7×4)) - 2(√(7×5))
= (16)-(4√5)-(4√7)-(2√35)
= 2{ 8-2√5-2√7-√35}
HOPE YOU UNDERSTAND AND MARK ME AS BRAINLIEST ✌️✌️✌️✌️
Answered by
1
Step-by-step explanation:
Similar questions
Science,
6 months ago
Science,
6 months ago
English,
1 year ago
Science,
1 year ago
Social Sciences,
1 year ago